2007
DOI: 10.1089/end.2006.9937
|View full text |Cite
|
Sign up to set email alerts
|

Second Prize: Frequency of Benign Renal Cortical Tumors and Histologic Subtypes Based on Size in a Contemporary Series: What to Tell our Patients

Abstract: This study examined the largest contemporary database evaluating the histologic type of renal lesions according to size. Approximately one fourth (26.3%) of lesions Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
58
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 28 publications
2
58
0
Order By: Relevance
“…The greatest frequency of benign lesions in renal tumors is smaller than 3 cm, as previously published (12)(13)(14). This study concludes that benign lesion sizes are much larger than those reported in other studies.…”
Section: Discussionsupporting
confidence: 82%
“…The greatest frequency of benign lesions in renal tumors is smaller than 3 cm, as previously published (12)(13)(14). This study concludes that benign lesion sizes are much larger than those reported in other studies.…”
Section: Discussionsupporting
confidence: 82%
“…Partial nephrectomy, open or laparoscopic technique, cryoablation, radiofrequency (RF) ablation and ultrasonic ablation have proven equally effective in the management of suitable neoplasms (5,8,(16)(17)(18)(19). RF and cryoablation in particular have achieved recurrence-free survival rates of up to 98.7% (16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical data from the recent urologic literature suggest that only 19.6 -43% of up to 4 cm lesions are benign (3)(4)(5). However, the differentiaPurpose: We evaluated the outcome and etiologies of small renal masses (less than 1 cm in size) discovered incidentally on 2 consecutive CTs that investigated nonurologic abdominal complaints.…”
Section: Original Article Introductionmentioning
confidence: 99%
“…[5][6][7][10][11][12][13] However, making a definitive diagnosis remains difficult. Recently, 2 studies have reported a higher proportion of benign disease for renal masses located on the periphery of the kidney compared to those located centrally within the kidney or at the renal hilum.…”
Section: Introductionmentioning
confidence: 99%